Correlation of Serum Immunoglobulin-E Level With Allergic Rhinitis Severity Based on Symptoms Classification - Widuri, Asti (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Allergic rhinitis (AR) is defined as an Imunoglobulin-E (IgE) -mediated reactions to inhaled allergens in atopic individual, with symptoms including runny nose, itchy nose, nasal congestion, and sneezing. Serum IgE was a reliable diagnostic marker for allergic rhinitis. This study aimed to reveal the correlation between IgE levels and the severity of allergic rhinitis symptoms according to the Allergic Rhinitis and Its Impacts on Asthma (ARIA) classification. Subject and Methods: A cross-sectional observational study was conducted involving 45 patients diagnosed with allergic rhinitis at the Otorhinolaryngology outpatient clinic. Subjects were identified through clinical evaluation, blood screening, and skin prick tests. Serum total IgE levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. Allergic rhinitis severity was categorized according to the ARIA classification into mild and moderate groups. Data were analyzed using the Chi-square test, and the association was presented as prevalence ratio (PR) with a 95% confidence interval (CI). Results: Forty-five patients with allergic rhinitis comprised of 30 females (66.70%) and 15 males (33.30%). The average IgE levels examination results were 204.24 IU/ml, with 23 subjects (48.89%) classified as standard, while those with higher-than-normal IgE levels were 22 subjects (53.49%). The Pearson chi-square test showed a significant correlation between higher-than-normal IgE levels and ARIA severity (PR = 1.65; 95% CI = 1.03–2.64; p = 0.045) Conclusion: Elevated serum IgE levels were significantly associated with greater allergic rhinitis severity based on ARIA classification and may serve as a useful supporting marker for disease severity assessment.